Traditional Lectures Actually Improve the Body of Knowledge, Skills, and Attitudes of Health Care Professional for Health Incident Reporting System - Souza Joao Luiz, Marcus Vinicius de; Varallo, Fabiana Rossi; Melgarejo, Celsa Raquel Villaverde [UNESP]; Nadai, Tales Rubens de; Carvalho Mastroianni, Patricia de [UNESP] (Sage Publications Inc, 2020)
Introduction: A solid patient safety culture lies at the core of an effective event reporting system in a health care setting requiring a professional commitment for event reporting identification. Therefore, health care settings should provide strategies in which continuous health care education comes up as a good alternative. Traditional lectures are usually more convenient in terms of costs, and they allow us to disseminate data, information, and knowledge through a large number of people in the same room. Taking in consideration the tight money budgets in Brazil and other countries, it is relevant to investigate the impact of traditional lectures on the knowledge, skills, and attitudes to incident reporting system and patient safety culture. Objective: The study aim was to assess the traditional lecture impact on the improvement of health care professional competency dimensions (knowledge, skills, and attitudes) and on the number of health care incident reports for better patient safety culture. Participants and Methods: An open-label, nonrandomized trial was conducted in ninety-nine health care professionals who were assessed in terms of their competencies (knowledge, skills, and attitudes) related to the health incident reporting system, before and after education intervention (traditional lectures given over 3 months). Results: All dimensions of professional competencies were improved after traditional lectures (P < .05, 95% confidence interval). Conclusions: traditional lectures are helpful strategy for the improvement of the competencies for health care incident reporting system and patient safety.
Keywords: adverse drug reactions reporting; monitoring; critical care; medication therapy management (MTM); human resources